Geology and Structural Description of Shakrok Anticline; Northern Iraq - Ahmed, Sally Hussin; Salman, Mahmood Abd ALAmeer (Iraqi Journal of Science, 2020)
The studied area is a part of the Arabian plate located within the High Folded Zone of the Zagros Fold-Thrust Belt in northeastern Iraq (Kurdistan Region). The Study area deals with the Shakrok Anticlines is located between Safin Mountain and Sork Mountain. These structures are formed during the Alpine Orogeny in Cretaceous-Tertiary period. Generally, the folded structures are trending NW-SE direction which is parallel to the main Zagros Orogenic trends. The exposed stratigraphic succession of the studied area that represented by 4 formations deposited from the Early Cretaceous which are Shiranish, Aqrah, Bekhme and Qamchuqa formations. Shakrok Anticline are asymmetrical, double plunging and verging toward northeast. This establishes that Merawa is a Tertiary continuation part of Cretaceous Shakrok Anticline, but there is a deflection in the direction of the fold axis that affected the Merawa Anticline due to the effect of strike slip fault addition to Lineament. Shakrok Anticline with Cretaceous successions formed due to the effect of Cretaceous and Tertiary folding phases. But Merawa Anticline with Tertiary succession that formed due to the effect of Tertiary folding phases. The high stress and intensity of the major fault on the southwestern limb rotated and overturned Tertiary successions and changed its dip toward NE. The differences in fold geometry, fold axis, axial surface, and curvilinear hinge imply that the structure formed as a result of two folding phases & lateral growth of folds that developed by changing the direction of the compressional tectonic processes due to Alpine Orogene of Zagros. The fold axis of Shakrok Anticline rotated 16o in anticlockwise trend from Merawa to Sork anticlines. Because of anticlockwise rotation of the Arabian plate due to its collision with Iranian and Anatolian plates.